2013
DOI: 10.1080/00224499.2012.681403
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Association between Pornography Use and Risky Sexual Behaviors: The Role of Early Exposure to Pornography and Sexual Sensation Seeking

Abstract: Among the suggested problems and harms associated with widespread pornography use among young people, risky sexual behaviors have been frequently mentioned. To further explore this public health concern, this article analyzed sexual sensation seeking (SSS) as a potential confounder of the association between pornography use and sexual risks using data collected in 2010 from a population-based sample of young Croatian adults aged 18 to 25 (n = 1,005). Significant, but small, correlations were found between the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
76
1
9

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 113 publications
(93 citation statements)
references
References 52 publications
7
76
1
9
Order By: Relevance
“…However, the additional variance explained by pornography-related variables on self-perceived effects was somewhat modest after controlling for included non-pornography-related variables. These findings are consistent with previous recent studies in this area which have also found that the additional explained variance of pornography-related variables on the outcomes investigated has been modest when other relevant non-pornography variables have been controlled for (Hald, Kuyper, et al, 2013;Peter & Valkenburg, 2011;SinkoviK c et al, 2013;Wright, 2013;Wright & Randall, 2012). This suggests that self-perceived effects of pornography consumption may be as much, or more, associated with factors other than pornographyrelated variables such as gender, sensation seeking, sexual attitude, and sexual behavior.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…However, the additional variance explained by pornography-related variables on self-perceived effects was somewhat modest after controlling for included non-pornography-related variables. These findings are consistent with previous recent studies in this area which have also found that the additional explained variance of pornography-related variables on the outcomes investigated has been modest when other relevant non-pornography variables have been controlled for (Hald, Kuyper, et al, 2013;Peter & Valkenburg, 2011;SinkoviK c et al, 2013;Wright, 2013;Wright & Randall, 2012). This suggests that self-perceived effects of pornography consumption may be as much, or more, associated with factors other than pornographyrelated variables such as gender, sensation seeking, sexual attitude, and sexual behavior.…”
Section: Discussionsupporting
confidence: 82%
“…Various previous research on pornography has consistently demonstrated that pornography-related variables predict levels of pornography consumption (see also Hald, 2006;SinkoviK c, Štulhofer, & BoL ziK c, 2013). Therefore, we find it plausible that pornography-related variables such as age of first exposure, acceptance of pornography, perceived realism of pornography, and pornography consumption will significantly predict self-reported and self-perceived effects of pornography consumption in this study.…”
supporting
confidence: 52%
See 2 more Smart Citations
“…However, a greater understanding is required to absorb what factors accelerate consumption rates and what are the reasons that consumption of pornography in women is greater after marriage. Further studies and research interventions are required in order to closely understand the patterns of consumptions of cyber pornographic content in women and how it is addictive and impacting the relationships in real life [22].…”
Section: Resultsmentioning
confidence: 99%